Pengembangan Sistem dan Model Bisnis Pengelolaan Lumpur Tinja di Kota Sawahlunto - Heantomas; Puti Sri Komala; Slamet Raharjo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Domestic wastewater management in Sawahlunto City is done by local system. About 75.5% of the houses use septic tanks, 4.1% are discharged into drainage channels, 4.5% are discharged into rivers, 15.9% have unknown location of domestic waste disposal. This study used primary data obtained from distribution of questionnaires to 100 respondents, interviews with stakeholders and field observations. Secondary data was obtained from related agencies. Evaluation of existing conditions through 5 aspects and determination of development strategy through SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and business model selection using business model canvas. The result was an average desludging production rate of 0.4 liters/person/day. About 64% of the respondents stated that they have never emptied their septic tanks and 56% of the respondents did not know about Integrated Pond Treatment (IPLT). The SWOT analysis shows that the project is in quadrant II, which means that the development strategy includes drafting regulations on domestic wastewater management, transferring the authority of desludging management to the PUPR office, continuous dissemination of information, and collaboration with the private sector in the dissemination of CSR (Corporate Social Responsibility). Based on the assessment of the business model canvas, the business model for the short term is co-composting and the business model for the long term is scheduled desludging management. Another alternative is to use fecal sludge as briquettes that can be used as a substitute fuel for coal in Sawahlunto City.